Seizures and EEG features in 74 patients with genetic‐dysmorphic syndromes. Issue 12 (24th September 2014) - Alfei, Enrico; Raviglione, Federico; Franceschetti, Silvana; D'Arrigo, Stefano; Milani, Donatella; Selicorni, Angelo; Riva, Daria; Zuffardi, Orsetta; Pantaleoni, Chiara; Binelli, Simona
<x xml:space="preserve">Abstract</x> Epilepsy is one of the most common findings in chromosome aberrations. Types of seizures and severity may significantly vary both between different conditions and within the same aberration. Hitherto specific seizures and EEG patterns are identified for only few syndromes. We studied 74 patients with defined genetic‐dysmorphic syndromes with and without epilepsy in order to assess clinical and electroencephalographic features, to compare our observation with already described electro‐clinical phenotypes, and to identify putative electroencephalographic and/or seizure characteristics useful to address the diagnosis. In our population, 10 patients had chromosomal disorders, 19 microdeletion or microduplication syndromes, and 32 monogenic syndromes. In the remaining 13, syndrome diagnosis was assessed on clinical grounds. Our study confirmed the high incidence of epilepsy in genetic‐dysmorphic syndromes. Moreover, febrile seizures and neonatal seizures had a higher incidence compared to general population. In addition, more than one third of epileptic patients had drug‐resistant epilepsy. EEG study revealed poor background organization in 42 patients, an excess of diffuse rhythmic activities in beta, alpha or theta frequency bands in 34, and epileptiform patterns in 36. EEG was completely normal only in 20 patients. No specific electro‐clinical pattern was identified, except for inv‐dup15, Angelman, and Rett syndromes. Nevertheless some specific conditions are described in detail, because of notable differences from what previously reported. Regarding the diagnostic role of EEG, we found that—even without any epileptiform pattern—the generation of excessive rhythmic activities in different frequency bandwidths might support the diagnosis of a genetic syndrome. © 2014 Wiley Periodicals, Inc.